THE EMPIRE OF THE FUTURE. - Bowker, Geoffrey C. (History & Theory, 2019)
This rich collection analyzes science in the archives over the past several thousand years. The chapters work together to tell stories of ambitious attempts to provide timeless data for science, which will be used for generations to come—ranging from ancient astronomy to geology to life‐logging and the development of web search. They also demonstrate convincingly that archives are powerful forces across the sciences—every science discussed has an archival base—which partly determine what kind of general knowledge claims can be made by future generations: it is hard to read an archive askance. The collection works best as a series of individual chapters, though some work is done to indicate where they speak to one another. It is a pity that there was not more input from archivists themselves in the project: their noninclusion means that some archival issues (especially what goes on with data after it gets into the archive—how it gets cleaned up, changed, reorganized) are treated somewhat lightly. The collection does provide a very useful set of tools for thinking about scientific archives. It is also an excellent introduction to the peculiarities of scientific archives—one that reflects back on the use of archives in history in general.